2005
DOI: 10.1080/1350485042000314352
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of betting market efficiency

Abstract: Previous studies of efficient markets in parimutuel betting isolated only one race characteristic, determining efficiency by comparing subjective to objective probabilities of different groupings. By incorporating regression analysis and looking at a wide range of race specific variables, this study is able to isolate various factors which influence efficiency. Using a data set of 5020 races at 18 US racetracks, a standard favourite-longshot bias was found, which diminishes for races with larger pools and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Mikesell and Zorn (1987) proposed that new games need to be added to ensure continued successful sales of existing games. Gramm and Owens (2005) found that larger pools increase the quality of the betting market. To maintain the momentum of lottery sales, Taipei Back inaugurated a new 6/49 numbers game (Big Lotto) in January 2004.…”
Section: Introductionmentioning
confidence: 97%
“…Mikesell and Zorn (1987) proposed that new games need to be added to ensure continued successful sales of existing games. Gramm and Owens (2005) found that larger pools increase the quality of the betting market. To maintain the momentum of lottery sales, Taipei Back inaugurated a new 6/49 numbers game (Big Lotto) in January 2004.…”
Section: Introductionmentioning
confidence: 97%
“…The bias is diminished if either the betting pool or the number of horses in the race is increased. (Busche and Hall, 1988;Gramm and Owens, 2005).…”
Section: G Summary and Discussion Of Biasesmentioning
confidence: 99%
“…Horseracing Factors: Previous research has indicated that the accuracy of forecasts derived from prices in horseracing markets may be influenced by race specific factors such as: number of runners (Gramm and Owens, 2005), whether the race is a handicap (Brown, 2016), the number of bends that horses encounter in the race (Johnson et al, 2010), the class of the race (Sung et al, 2012), whether the race is run at a weekend (Sung et al, 2012), whether the race is the first or last of the day at a particular racetrack (Johnson and Bruce, 1993) and the bookmaker commission charged on the race (Vaughan Williams and Paton, 1998). We include all these factors in the regression as control variables, together referred to as 'Horseracing Factors'.…”
Section: Assessing Influence Of Environmental Conditions On Forecast mentioning
confidence: 99%